Responses to weaning in two pig lines divergently selected for residual feed intake depending on diet - Gilbert, Hélène (J Anim Sci, 2019)
Weaning is a stress every piglet has to face. It is a main cause of antibiotic uses due to digestive disorders. In this study, response to weaning was analyzed in pigs from two lines divergently selected for residual feed intake (RFI) during growth. A total of 132 pigs from each line, housed per line and diet in conventional postweaning units of 12 castrated males and 12 females, were fed either a conventional control (two successive diets) or a complex (three successive diets) dietary sequence during the postweaning period (4 to 10 wk of age). BWs were recorded at weaning (days 0 and 28 of age), days 1, 2, 6, 12, 19, 26, and 42 (10 wk of age), and at 23 wk of age. Feces texture was examined before weaning (day −1), at day 1, 2, 6, 12, and 19. Feed intake was recorded at pen level from days 0 to 42 after weaning, and individually thereafter. Plasma was collected after blood samplings at days −1, 6, 19, and 42 on half of the piglets: all piglets of a given sex in each pen were sampled, to achieve a balanced number across factors. Pigs of the low RFI (LRFI) line were heavier at weaning, had greater glucose concentration, and lower levels of diarrhea at days 1 and 2 than pigs from the high RFI (HRFI) line (P < 0.01). At day 42, there was no BW difference between lines, and G:F ratio did not differ between lines (P = 0.40). The LRFI pigs had lower feed intake and growth rate from day 0 to day 19 (P < 0.005), and greater plasma concentration of non-esterified fatty acid (P < 0.001), indicating an increased mobilization of body lipids and proteins immediately after weaning compared with HRFI pigs. They also had greater levels of diarrhea at day 6 (22% for LRFI vs. 14% for HRFI, P = 0.002), but the concentration of plasma haptoglobin did not indicate acute inflammation. The complex diet sequence improved feed intake and growth, and reduced diarrhea, mainly in the LRFI line (P < 0.001). To conclude, pigs from the LRFI line were more negatively affected by weaning stress, but managed to recover afterwards. The complex diet sequence ameliorated some of the negative effects that weaning had on the LRFI pigs, but limited effects of nursery period feeding sequence on growth performance were observed during the growing-finishing period.